Krytyka stalinizmu w 1950 roku: Andre Bazina analiza kina epoki stalinowskiej - KLEBERG, LARS (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Criticism of Stalinism in 1950: André Bazin’s analysis of Stalinist era cinema The main purpose of the article is to analyze attempts at a critique of Stalinism in cinematography in the work of the outstanding French film theorist and critic Andre Bazin. Through a comparison of Bazins opinions with statements by his adversary Georges Sadoul, Lars Kleberg shows the vast context of the debate on this topic, which occurred in France in the 1950s.